Feature-Trace: Generating Operational Profile and Supporting Testing Prioritization from BDD Features - Fazzolino, Rafael; Rodrigues, Genaína Nunes (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2019: Anais do XXXIII Simpósio Brasileiro de Engenharia de Software, 2019)
Operational Profiles provide quantitative information about how the software will be used, which supports highlighting those software components more sensitive to reliability based on their profile usage. However, the generation of Operational Profiles usually requires a considerable team effort to liaise requirements specification until their reification into expected software artifacts. In this sense, it becomes paramount in the software life cycle the ability to seamlessly or efficiently perform traceability from requirement to code, embracing the testing process as a means to ensure that the requirements are satisfiably covered and addressed. In this work, we propose the Feature-Trace approach which merges the advantages of the Operational Profile and the benefits of the requirements-to-code traceability present in the BDD (Behavior-Driven Development) approach. The primary goal of our work is to use the BDD approach as an information source for the semi-automated generation of the Operational Profile. The proposed approach was evaluated on the Diaspora software, on a GitHub open source software. The case study revealed that the Feature-Trace approach is capable of extracting the operational profile seamlessly from the specified Diaspora's BDD features as well as obtaining and presenting vital information to guide the process of test cases prioritization.